2015
DOI: 10.1099/jmm.0.000162
|View full text |Cite
|
Sign up to set email alerts
|

Genes encoding ten newly designated OXA-63 group class D β-lactamases identified in strains of the pathogenic intestinal spirochaete Brachyspira pilosicoli

Abstract: The anaerobic spirochaete Brachyspira pilosicoli colonizes the large intestine of birds and mammals, including human beings, and may induce colitis and diarrhoea. B. pilosicoli has a recombinant population structure, and strains show extensive genomic rearrangements and different genome sizes. The resident chromosomal gene bla OXA-63 in B. pilosicoli encodes OXA-63, a narrow-spectrum group IV class D b-lactamase. Genes encoding four OXA-63 variants have been described in B. pilosicoli, and the current study wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 23 publications
0
3
0
Order By: Relevance
“…If patients are symptomatic after ruling out of other diseases, eradication therapy should be considered. It is common to use metronidazole or amoxicillin as therapeutic agents (1,11,23), but in recent years, the efficacy of penicillin has decreased due to an increase in β-lactamase-producing strains (24).…”
Section: Discussionmentioning
confidence: 99%
“…If patients are symptomatic after ruling out of other diseases, eradication therapy should be considered. It is common to use metronidazole or amoxicillin as therapeutic agents (1,11,23), but in recent years, the efficacy of penicillin has decreased due to an increase in β-lactamase-producing strains (24).…”
Section: Discussionmentioning
confidence: 99%
“…High MICs to ampicillin and amoxicillin + clavulanic acid was observed in B. hyodysenteriae, B. hampsonii and B. pilosicoli. While β-lactams are not used to treat Brachyspira-associated infections, the use of penicillin for treating other infections in pigs may have contributed to the selection of resistance to these drugs in Brachyspira [59][60][61]. Previous studies found that B. pilosicoli with high β-lactam drugs MICs possessed the OXA-63 gene, a class D β-lactamase [59].…”
Section: Plos Onementioning
confidence: 99%
“…Most published studies have focused on the association between single nucleotide polymorphisms (SNPs) in genes encoding ribosomal RNA and ribosomal proteins and increased MIC to drugs that act by inhibiting protein synthesis inhibitors, including macrolides, lincosamides, pleuromutilins, doxycycline, chloramphenicol, and florfenicol (Pringle et al 2004(Pringle et al , 2007Hidalgo et al 2011;Verlinden et al 2011;Hillen et al 2014). Narrow-spectrum ␤-lactamases, including 13 enzymes related to OXA-63, have also been identified in B. pilosicoli (Meziane-Cherif et al 2008;Mortimer-Jones et al 2008;La et al 2015). Differences in intrinsic resistance, even between closely related bacteria, can inform treatment decisions based on accurate organism identification, for example, differences in the intrinsic resistance to vancomycin of Enterococcus gallinarum but not Enterococcus faecalis or E. faecium (CLSI 2017).…”
Section: Objective Measures Of Resistancementioning
confidence: 99%